From Faith To Philanthropy: The Role Of I?s?n And Egalitarianism In Determining Cash Waqf Intention Among Generations Y-Z In Malaysia - Wan Rasyidah Wan Nawang; Nurul Ain Azri (International Shari’ah Research Academy for Islamic Finance (ISRA) Institute, 2026)
Purpose — The aim of this study is to determine how cash waqf intention is affected by religiosity, perceived iḥsān, and Islamic egalitarianism, as well as how perceived iḥsān and Islamic egalitarianism serve as mediators in the said relationships. Design/Methodology/Approach — The study involved 208 respondents from Generations Y-Z (Gen Y-Z), aged 18 to 43 in Malaysia. The respondents were selected via purposive sampling while the derived data were scrutinised utilising Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings — The study reveals that perceived iḥsān and Islamic egalitarianism are significantly influenced by religiosity, but that religiosity has no direct effect on cash waqf intention. Additionally, both perceived iḥsān and Islamic egalitarianism significantly affect cash waqf intention, acting as mediators between the said intention and religiosity. This indicates that religiosity influences cash waqf intention through these intermediary factors. Originality/Value — The novel contribution of this research lies in demonstrating the interconnected pathways through which religiosity influences cash waqf intention, as well as the roles of perceived iḥsān and Islamic egalitarianism as mediators in shaping cash waqf intention. Unlike earlier studies that positioned religiosity as a mediator between perceived iḥsān, Islamic egalitarianism, and intention to contribute to cash waqf, this research differs by treating religiosity as the independent variable, with perceived iḥsān and Islamic egalitarianism as mediators, thereby reversing the causal structure and offering a new conceptual perspective. Research Limitations/Implications — The study’s generalisability is limited due to its student-dominated sample and cross-sectional design, which captures data at a single point in time. Future research should consider diverse samples and longitudinal approaches to improve the robustness of the findings. Practical Implications — The study recommends that religious leaders, Islamic organisations, and policymakers should launch campaigns that highlight the religious and moral significance of cash waqf, while also promoting the values of iḥsān and Islamic egalitarianism to boost contributions. Furthermore, the implementation of flexible, income-based donation models could encourage wider participation by allowing individuals to contribute based on their financial capacity, thereby enhancing public engagement and charitable giving, particularly within the context of cash waqf.